Rearing Hoven’s Carp (Leptobarbus hoevenii) by Feeding Fermented with Herbal Supplements in a Recirculation System - Abdul Haris; Iskandar Putra; Rusliadi Rusliadi (Jurnal Akuakultur SEBATIN, 2023)
Study aims to determine the best dose in rearing hoven’s carp (Leptobarbus hoevenii) by feeding fermented feed with herbal supplements in a recirculation system. This research was conducted from 16 January - 24 February 2022 at the UPT Experimental Pond of the Faculty of Fisheries and Marine Scnie, University of Riau. The container used was a black tub with a volume of 100 L as many as 15 units with a stocking density of 20 individuals / 80 L. This study used a one-factor completely randomized design (CRD) method with five levels of treatment and three replications. The level of treatment applied in this study was P0= without giving herbal supplements (control), P1 = doses of herbal supplements 100 ml / kg of feed, P2 = doses of herbal supplements 200 ml / kg of feed, P3 = dose of herbal supplements 300 ml/kg of feed and P4 = doses of herbal supplements 400 ml/kg of feed. The results showed that giving herbal supplements to feed with different doses had a significant effect (P <0.05) on growth but had no significant effect (P> 0.05) on the survival of leptobarbus hoevenii. The best treatment was found at the herbal supplement dosage of 300 ml/kg of feed, which resulted in absolute weight growth (5.52 g), absolute length growth (4.55 cm), specific growth rate (2.92 %), feed conversion ratio (1.80), survival rate (100%), feed digestibility (63.77%) , protein digestibility (80.16%).